Implementation of Online Single Submission System at Jakarta Investment Coordinating Board - Aos Yuli Firdaus; Aberar Grudino; Winny Artha Sanjaya (Publikasi Indonesia, 2022)
The Online Single Submission (OSS) is a system that integrates all business licensing services under the authority of the Minister Institutions, Governors, or Regents/Mayors conducted electronically to make it easier for business actors to reduce the convoluted bureaucracy - convoluted and lengthy. This research aims to find out how to implement the Online Single Submission system at the Planting Coordinating Board Jakarta Capital. Collection technique data using interviews, observation, documentation and literature study. Analysis data using the Miles and Huberman model, namely data collection, reduction data, data presentation and verification. The results of this study that the implementation of the system Online Single Submission (OSS) at the Central Investment Coordinating Board in Jakarta has not been running well and optimally from communication, resources and disposition. There is still a lack of socialization to all levels of society from other agencies or regions that have caused disharmony from the central government to the provinces. It has not accommodated all complaints from business actors at the regional level due to the limited capacity provided. Lack of supporting facilities such as the availability of compliant services such as the LAPOR! Unable to provide information or active solutions to the entire community of business actors effectively.